Observational Effects on the Food Preferences of Children With Autism Spectrum Disorder. (March 2021) - Cihon, Joseph H.; Weiss, Mary Jane; Ferguson, Julia L.; Leaf, Justin B.; Zane, Thomas; Ross, Robert K.
Research addressing food selectivity has involved intrusive techniques such as escape extinction. It is possible that observational learning methods employed in previous studies could provide the desired results with respect to food selectivity without the need for invasive physical interventions. The purpose of this study was to evaluate the effectiveness of an observational learning procedure on the selection of food items of three children diagnosed with autism spectrum disorder. Baseline consisted of a simple task after which a choice was presented between high- and low-preferred foods. The intervention consisted of observing an adult engage in the same task and selecting the low-preferred food while making favorable comments and engaging with the food in novel ways. The results of a reversal design demonstrated that selection of the low-preferred food only occurred following the introduction of the intervention, and all three participants engaged in flexible responding as a result of the intervention.